The Construction of the Maras - Antonia Does (Graduate Institute Publications, 2013)
High levels of crime and violence in Central America's northern triangle are a major preoccupation of politicians, policy-makers and citizens. Public authorities in El Salvador, Honduras and Guatemala have sought repressive measures to increase public safety and to contain such violence, for which youth gangs (maras) are principally held responsible. Substantiated by interviews with key stakeholders in Geneva, Switzerland, this desk review offers a comprehensive understanding of the motivatio...